Molecular nature and physiological role of the mitochondrial calcium uniporter channel - Alevriadou, B Rita; Patel, Akshar; Noble, Megan; Ghosh, Sagnika; Gohil, Vishal M; Stathopulos, Peter B; Madesh, Muniswamy (American Journal of Physiology: Cell Physiology, 2021)
Calcium (Ca ) signaling is critical for cell function and cell survival. Mitochondria play a major role in regulating the intracellular Ca concentration ([Ca ] ). Mitochondrial Ca uptake is an important determinant of cell fate and governs respiration, mitophagy/autophagy, and the mitochondrial pathway of apoptosis. Mitochondrial Ca uptake occurs via the mitochondrial Ca uniporter (MCU) complex. This review summarizes the present knowledge on the function of MCU complex, regulation of MCU channel, and the role of MCU in Ca homeostasis and human disease pathogenesis. The channel core consists of four MCU subunits and essential MCU regulators (EMRE). Regulatory proteins that interact with them include mitochondrial Ca uptake 1/2 (MICU1/2), MCU dominant-negative β-subunit (MCUb), MCU regulator 1 (MCUR1), and solute carrier 25A23 (SLC25A23). In addition to these proteins, cardiolipin, a mitochondrial membrane-specific phospholipid, has been shown to interact with the channel core. The dynamic interplay between the core and regulatory proteins modulates MCU channel activity after sensing local changes in [Ca ] , reactive oxygen species, and other environmental factors. Here, we highlight the structural details of the human MCU heteromeric assemblies and their known roles in regulating mitochondrial Ca homeostasis. MCU dysfunction has been shown to alter mitochondrial Ca dynamics, in turn eliciting cell apoptosis. Changes in mitochondrial Ca uptake have been implicated in pathological conditions affecting multiple organs, including the heart, skeletal muscle, and brain. However, our structural and functional knowledge of this vital protein complex remains incomplete, and understanding the precise role for MCU-mediated mitochondrial Ca signaling in disease requires further research efforts.